Legal Status of Shareholder Agreements on GMS Quorum Deviations - Susiani; Budi Santoso; Satria Amiputra Amimakmur (YURISDIKSI : Jurnal Wacana Hukum dan Sains, 2026)
This study examines the legal status of the shareholders agreement, which regulates the quorum of the General Meeting of Shareholders (GMS) differently from the provisions of the Limited Liability Company Law (UUPT) and the Company's Articles of Association (AD), with a case study of a share ownership dispute and the implementation of the GMS at PT Indo Mineralita Prima. The dispute began with the sale and purchase of shares based on a share pledge agreement, which then resulted in a secret transfer of ownership and the implementation of the GMS without notification to one of the shareholders. The shareholders had previously agreed to a shareholders agreement that required that changes to the Board of Directors and Board of Commissioners must be approved by 100% of the shareholders. However, in practice, some shareholders made changes to the company's structure, share transfers, and capital increases without following these provisions. This gave rise to a lawsuit for breach of contract by PT Investasi Internasional Indonesia, as the 28% shareholder, who felt aggrieved due to share dilution and decision-making without a valid quorum. The Panel of Judges in its decision stated that the defendants had committed a breach of contract and annulled several GMS deeds as a result of the violation of the shareholders agreement. However, the author's analysis shows that the shareholder agreement cannot override the Company Law and the Articles of Association, so that the 100% quorum requirement, which is not regulated in the Articles of Association, is not binding on the company. Therefore, the shareholder agreement is only legally binding on the parties as long as it does not conflict with statutory regulations and the Articles of Association. This research emphasizes the importance of harmonizing private shareholder agreements and corporate law to create legal certainty in corporate governance.